TRANSFORMATIVE LEADERSHIP IN THE DIGITAL ERA: A SYSTEMATIC ANALYSIS OF SOCIAL IMPLICATIONS FOR FUTURE-READY ORGANIZATIONS - Delfi, Asri; Yunianto, Eko; Sariyono, Eko Budi; Sukandar; Humokor, Edwin Johanis; Simbolon, Octorolas; Astuti, Dwi (Journal of Scientech Research and Development, 2024)
This research examines the evolving nature of transformative leadership in digitally transformed organizations through a systematic analysis of scholarly literature from 2004 to 2024. While digital transformation has fundamentally altered organizational landscapes, existing leadership frameworks often fail to address the complex interplay between technological innovation, regulatory compliance, and social responsibility. Through a comprehensive analysis of publications indexed in the Scopus database, this study identifies three distinct phases in the evolution of leadership paradigms: Traditional Leadership (2004-2012), Digital Transition (2013-2019), and Integrated Leadership (2020-2024). The research introduces the "Digital Leadership Trilogy" framework, demonstrating that leaders who effectively integrate technological competence, regulatory awareness, and social responsibility achieve 47% higher success rates in digital transformation initiatives. Statistical analysis reveals a strong correlation (r = 0.78, p < 0.001) between leaders' emphasis on social responsibility and successful long-term transformation outcomes, while organizations with high regulatory awareness showed 64% fewer compliance-related disruptions. The findings contribute to both theoretical understanding and practical application of leadership development, suggesting that future-ready organizations require leaders capable of navigating the synergistic relationship between technological advancement, regulatory frameworks, and social impact. This research provides valuable insights for developing integrated leadership frameworks that address the multifaceted challenges of the digital era.